Evolutionary Consequences, Constraints and Potential of Polyploidy in Plants - Weiss-Schneeweiss, H.; Emadzade, K.; Jang, T.-S.; Schneeweiss, G.M. (Cytogenetic and genome research, 2013)
Polyploidy, the possession of more than 2 complete genomes, is a major force in plant evolution known to affect the genetic and genomic constitution and the phenotype of an organism, which will have consequences for its ecology and geography as well as for lineage diversification and speciation. In this review, we discuss phylogenetic patterns in the incidence of polyploidy including possible underlying causes, the role of polyploidy for diversification, the effects of polyploidy on geographical and ecological patterns, and putative underlying mechanisms as well as chromosome evolution and evolution of repetitive DNA following polyploidization. Spurred by technological advances, a lot has been learned about these aspects both in model and increasingly also in nonmodel species. Despite this enormous progress, long-standing questions about polyploidy still cannot be unambiguously answered, due to frequently idiosyncratic outcomes and insufficient integration of different organizational levels (from genes to ecology), but likely this will change in the near future. See also the sister article focusing on animals by Choleva and Janko in this themed issue.